Do Major and Emerging Economies Co-Integrate with, Influence Over, or Make a Volatility Spillover Effect on the Indian Stock Market? An Empirical Analysis - Kannan, R. Kumara; Jesiah, Selvam (Indian Journal of Research in Capital Markets, 2024)
Purpose : In order to protect the poor and rural investors, who make up 30% of all investors, it became imperative to look into the degree of dependency between the Indian stock market and other major economic stock markets once the pandemic began to threaten the world. There were 10 million investors in rural India out of 33.7 million investors in the country overall. Thus, the purpose of this study was to examine how India’s economic reforms have affected other major economies and how dependent they are on India. Methodology : The Augmented Dickey–Fuller test was used to determine whether a unit root exists. The Johnson co-integration test, Granger causality test, GARCH Model, serial correlation test, heteroskedasticity test, and Histogram normality test were used to determine whether an ARCH effect existed. The GARCH, GARCH M, and EGARCH models were used to determine whether volatility spillover effects existed. Findings : We discovered that with the help of these instruments, the Indian stock market is more dependent on the Japanese stock market than it is on the Russian stock market. Practical Implications : This would make it possible for government organizations to draft trading laws that would permit investors from both home and abroad to transact on the Indian stock exchanges. The co-integration era might influence how the government writes laws governing investment strategies and capital market investment restrictions. Originality : A thorough analysis of the post-reform period is necessary, in contrast to earlier research on co-integration, as this will provide a comprehensive picture of the interdependence between the markets. A substantial sample of economies for the study must be gathered, which is another requirement. Three hundred eighty-four monthly data points were gathered throughout the post-economic reform era in order to compare 20 economies with India.